Propiedad distributiva de la multiplicación - Mejia Maguiña, Margot Nelly (2018)
Through the development of this Learning Session it is intended to build on the student the information necessary to solve exercises with the Distributive Property of Multiplication. It will take into account the way in which students analyze, understand the information to solve exercises and problems with the Distributive Property of Multiplication, if they are able to develop an exercise that integrates operations such as addition and multiplication. The student will be encouraged to work fun math, where they learn by playing, to demonstrate the ability and competence they have to solve problems with the Distributive Property of Multiplication with ease, to socialize their exercises, to give them the opportunity to value their learning, organize what has been learned and arouse the curiosity that mathematics is learned in a fun way. The motivating reading is the "The Goblin and the Seven Colors" waiting for the objectives set.